Electronic component and manufacturing method thereof

JP2024032790A5Active Publication Date: 2025-04-01RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024004604
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-09-14
Filing Date
2024-01-16
Publication Date
2025-04-01
Estimated Expiration
2039-09-05

AI Technical Summary

Technical Problem

Existing methods for forming copper interconnects on polymer molded bodies face challenges in productivity due to the use of expensive catalysts and require laser irradiation and electroless copper plating, while methods involving metal paste application suffer from insufficient adhesion between the polymer and metal wiring.

Method used

A method involving the application of a metal paste containing metal particles in a predetermined pattern on a polymer molded body, followed by sintering, and subsequent steps of applying a solder paste with resin, placing an electronic element, and forming a solder layer and resin layer to enhance adhesion.

Benefits of technology

This method allows for easy formation of metal wiring with improved adhesion to the polymer molded body, eliminating the need for costly catalysts and complex processes like laser irradiation and electroless copper plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an electronic component with high adhesive strength and a manufacturing method thereof, facilitating a formation of metal wiring and a mounting of electronic elements.SOLUTION: A manufacturing method of an electronic component according to the present invention includes a first step of applying a metal paste containing metal particles in a predetermined pattern onto a polymer molded body to form a metal paste layer, a second step of forming metal wiring by sintering the metal particles, a third step of applying a solder paste containing solder particles and a resin component onto the metal wiring to form a solder paste layer, a fourth step of placing an electronic element on the solder paste layer, and a fifth step of heating the solder paste layer to form a solder layer that joins the metal wiring and the electronic element, and a resin layer that covers at least a portion of the solder layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electronic component and a method for manufacturing an electronic component. [Background technology]

[0002] In recent years, a method for forming a metal layer by plating on the surface of a polymer molded body for the purpose of functional and / or decorative surface processing has been studied. For example, when forming metal wiring on a polymer molded body, it is necessary to form the metal wiring in a predetermined pattern, so laser direct structuring (LDS) is useful as a method for selectively plating metal. For example, when forming copper wiring by LDS, a laser is irradiated to the part of a polymer molded body containing a catalyst where copper wiring is to be formed to activate the catalyst, so that electroless copper plating can be selectively applied to the catalyst (only to the part where copper wiring is to be formed), and as a result, copper wiring having a predetermined pattern can be formed (for example, Patent Document 1). On the other hand, a method for easily forming copper wiring by applying a paste containing copper on a polymer molded body and baking it has been proposed (for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-149347 A [Patent Document 2] JP 2017-123254 A Summary of the Invention [Problem to be solved by the invention]

[0004] The method of forming copper wiring by LDS has problems in terms of productivity, since the catalyst-containing polymer is expensive and the processes of laser irradiation and electroless copper plating are required. On the other hand, the method of simply forming metal wiring by applying a metal paste onto a polymer molded body and baking it does not obtain sufficient adhesion between the polymer molded body and the metal wiring, and the adhesive strength of electronic components is likely to decrease.

[0005] Therefore, an object of one aspect of the present invention is to provide an electronic component with high adhesive strength and a method for manufacturing an electronic component, which allows for easy formation of metal wiring and mounting of electronic elements. [Means for solving the problem]

[0006] One aspect of the present invention is a method for manufacturing an electronic component, comprising: a first step of applying a metal paste containing metal particles in a predetermined pattern onto a polymer molded body to form a metal paste layer; a second step of forming metal wiring by sintering the metal particles; a third step of applying a solder paste containing solder particles and a resin component onto the metal wiring to form a solder paste layer; a fourth step of arranging an electronic element on the solder paste layer; and a fifth step of heating the solder paste layer to form a solder layer that joins the metal wiring and the electronic element and also to form a resin layer that covers at least a portion of the solder layer.

[0007] In this manufacturing method, since the metal paste is applied in a predetermined pattern (a pattern corresponding to the metal wiring), a polymer containing a catalyst is not required, and the steps of laser irradiation and electroless copper plating can be omitted. In addition, in this manufacturing method, the metal paste is baked to form a metal wiring, and then a solder paste is applied onto the metal wiring. After an electronic element is placed on the solder paste, the solder paste is heat-treated, so that the metal wiring and the electronic element are joined via a solder layer, and a resin layer is formed around the periphery of the solder layer, thereby improving the adhesion between the polymer molded body and the metal wiring.

[0008] In the second step, the metal wiring may have voids. In the third step, at least a part of the voids in the metal wiring may be filled with a resin component.

[0009] The solder particles may be a tin-containing component, and may be an alloy made of an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, or an Sn-Cu alloy.

[0010] The metal particles may be composed of at least one metal selected from the group consisting of copper, nickel, palladium, gold, platinum, silver and tin. The metal particles may include first metal particles having a particle size of 2.0 μm or more and second metal particles having a particle size of 0.8 μm or less.

[0011] The polymer molding may consist of a liquid crystal polymer or polyphenylene sulfide.

[0012] The electronic element may have an electrode containing at least one metal selected from the group consisting of copper, nickel, palladium, gold, platinum, silver and tin on its outermost surface, and in the fourth step, the electronic element may be arranged so that the electrode is in contact with the solder paste layer.

[0013] Another aspect of the present invention is an electronic component comprising: a polymer molded body; metal wiring formed on the polymer molded body and consisting of a sintered body of metal particles; an electronic element arranged on the metal wiring; a solder layer joining the metal wiring and the electronic element; and a resin layer consisting of a cured product of a resin component that covers at least a portion of the solder layer. Effect of the Invention

[0014] According to one aspect of the present invention, it is possible to easily form metal wiring and mount electronic elements, and obtain good adhesion between the metal wiring and a polymer molded article. [Brief description of the drawings]

[0015] [Figure 1]1A to 1C are schematic cross-sectional views illustrating a method for manufacturing an electronic component according to an embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining a joint between a metal wiring and a polymer molded body in an electronic component. [Diagram 3] 1A to 1C are schematic cross-sectional views illustrating a method for manufacturing an electronic component according to an embodiment. [Figure 4] 1 is a SEM image showing an example of a cross section of metal wiring made of a sintered body of metal particles. [Diagram 5] 1A to 1C are schematic diagrams illustrating a method for manufacturing an electronic component in an embodiment. [Figure 6] FIG. 2 is a cross-sectional view of an electronic component produced in an example. [Figure 7] FIG. 2 is a cross-sectional view of an electronic component produced in an example. [Figure 8] 1A to 1C are schematic diagrams illustrating a method for manufacturing an electronic component in an embodiment. [Figure 9] FIG. 2 is a cross-sectional view of an electronic component produced in an example. [Figure 10] FIG. 2 is a schematic diagram for explaining a method for measuring shear strength in the examples. [Figure 11] FIG. 2 is a schematic diagram for explaining a method for measuring shear strength in the examples. [Figure 12] FIG. 1 is a cross-sectional image of an electronic component produced in a comparative example. [Figure 13] FIG. 1 is a cross-sectional image of an electronic component produced in a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following embodiments. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted.

[0017] The method for manufacturing an electronic component of this embodiment includes a first step of applying a metal paste containing metal particles in a predetermined pattern onto a polymer molded body to form a metal paste layer; a second step of forming metal wiring by sintering the metal particles; a third step of applying a solder paste containing solder particles and a resin component onto the metal wiring to form a solder paste layer; a fourth step of arranging an electronic element on the solder paste layer; and a fifth step of heating the solder paste layer to form a solder layer that joins the metal wiring and the electronic element and also form a resin layer that covers at least a portion of the solder layer.

[0018] The metal particles preferably contain at least one metal selected from the group consisting of copper, nickel, palladium, gold, platinum, silver and tin. Since sintering is likely to occur at low temperatures, the metal particles preferably contain copper or silver, and more preferably contain copper from the viewpoint of suppressing migration when fine wiring is formed. In consideration of low-temperature sintering and material costs, it is more preferable to use silver-coated copper particles as the metal particles. The metal particles may be used alone or in combination of two or more types. In addition, the metal particles may contain two or more types of metal particles having different particle sizes, for example, first metal particles having a particle size of 2.0 μm or more and second metal particles having a particle size of 0.8 μm or less.

[0019] Fig. 1 is a schematic diagram showing a method for manufacturing an electronic component according to an embodiment. A case where copper particles are used as metal particles for forming metal wiring will be described. In this manufacturing method, first, a copper paste containing copper particles is applied in a predetermined pattern onto a polymer molded body to form a metal (copper) paste layer (first step). In the first step, a polymer molded body 1 is first prepared (preparation step) as shown in Fig. 1(a).

[0020] The polymer molded body 1 is a molded body molded by a known method using a polymer such as polyamide (PA), polybutylene terephthalate (PBT), polycarbonate (PC), polyetherimide (PI), polyphenylene sulfide (PPS), polyether ether ketone (PEEK), liquid crystal polymer (LCP), etc. The shape and size of the polymer molded body are arbitrary. The polymer molded body 1 is preferably made of liquid crystal polymer (LCP) or polyphenylene sulfide (PPS).

[0021] (First step) In the first step, following the preparation step, as shown in (b) of Fig. 1, a copper paste is applied in a predetermined pattern (on the portion where copper wiring is to be formed) onto the polymer molded body 1 to form a copper paste layer 2 (forming step). The copper paste is applied by, for example, screen printing, transfer printing, offset printing, jet printing, a dispenser, a jet dispenser, a needle dispenser, a comma coater, a slit coater, a die coater, a gravure coater, a slit coat, letterpress printing, intaglio printing, gravure printing, stencil printing, soft lithography, a bar coat, an applicator, a particle deposition method, a spray coater, a spin coater, a dip coater, an electrochemical coating, or the like.

[0022] The thickness of the copper paste layer may be 1 μm or more, 2 μm or more, 3 μm or more, 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more, and may be 3000 μm or less, 1000 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less.

[0023] In the forming step, the copper paste layer 2 provided on the polymer molded body 1 may be appropriately dried in order to suppress the flow of copper particles during sintering and the generation of voids. The gas atmosphere during drying may be air, an oxygen-free atmosphere such as nitrogen or a rare gas, or a reducing atmosphere such as hydrogen or formic acid. The drying method may be drying by leaving at room temperature, drying by heating, or drying under reduced pressure. For example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate pressing device, or the like can be used for drying by heating or drying under reduced pressure. The temperature and time of drying may be appropriately adjusted according to the type and amount of the dispersion medium used. The temperature of drying may be, for example, 50°C or higher and 180°C or lower. The time of drying may be, for example, 1 minute or more and 120 minutes or less.

[0024] The copper paste contains, as copper particles, first copper particles having a particle size (maximum diameter) of, for example, 2.0 μm or more. The particle size (maximum diameter) of the first copper particles is 2.0 μm or more, and may be, for example, 3.0 μm or more. The particle size of the first copper particles may be 20 μm or less, or may be 10 μm or less. The average particle size (average maximum diameter) of the first copper particles may be 1.0 μm or more or 3 μm or more, and may be 20 μm or less, or 10 μm or less, from the viewpoint of further suppressing breakage of the obtained wiring due to thermal stress.

[0025] The particle size and average particle size of the first copper particles can be obtained, for example, from an SEM image of the particles. A method for calculating the particle size (maximum diameter) of the first copper particles from an SEM image is exemplified. A powder of the first copper particles is placed on a carbon tape for SEM with a spatula to prepare a sample for SEM. This sample for SEM is observed at 5000 times magnification with an SEM device. A rectangle circumscribing the first copper particle in the SEM image is drawn with image processing software, and the long side of the rectangle is taken as the particle size (maximum diameter) of the particle. This measurement is performed on 50 or more first copper particles using multiple SEM images, and the average particle size (average maximum diameter) is calculated.

[0026] The volume average particle diameter of the first copper particles may be 2.0 μm or more or 3.0 μm or more, and may be 50 μm or less, 20 μm or less, or 10 μm or less. In this specification, the volume average particle diameter means a 50% volume average particle diameter. When determining the volume average particle diameter of the copper particles, the copper particles as a raw material or dried copper particles obtained by removing volatile components from copper paste are dispersed in a dispersion medium using a dispersant, and the resulting dispersion medium is measured using a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (Shimadzu Corporation product name: SALD-7500nano). When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, etc. can be used as the dispersion medium.

[0027] The first copper particles are preferably flake-shaped. In this case, the first copper particles are oriented approximately parallel to the surface of the copper paste, which suppresses the volumetric shrinkage when the copper particles in the copper paste are sintered, and the breakage of the obtained wiring due to thermal stress is further suppressed. In addition, although the reason is unclear, the adhesion between the copper wiring and the polymer molded body is further improved.

[0028] The aspect ratio of the first copper particles may be 4 or more, or may be 6 or more. If the aspect ratio is within the above range, the first copper particles in the copper paste are easily oriented parallel to the surface of the copper paste, and the volume shrinkage when the copper particles in the copper paste are sintered can be suppressed. Therefore, the breakage of the obtained wiring due to thermal stress can be further suppressed. The aspect ratio (major axis / thickness) of the copper particles in the copper paste can be obtained, for example, by observing an SEM image of the particles and measuring the major axis and thickness.

[0029] The copper paste preferably contains first copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of at least 4. When the average particle size and aspect ratio of the first copper particles are within the above ranges, the volumetric shrinkage when the copper particles in the copper paste are sintered can be sufficiently reduced, and breakage of the obtained wiring due to thermal stress can be further suppressed.

[0030] The copper paste may contain copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of less than 2, but the content of the copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of less than 2 is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, per 100 parts by mass of the first copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of 4 or more. By limiting the content of the copper particles having an average particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of less than 2, the first copper particles in the copper paste are easily oriented approximately parallel to the coating surface of the copper paste, and the volumetric shrinkage when the copper particles in the copper paste are sintered can be more effectively suppressed. This makes it easier to suppress breakage of the resulting wiring due to thermal stress. In order to make such effects easier to obtain, the content of the copper particles having an average particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of less than 2 may be 20 parts by mass or less, 10 parts by mass or less, or even 0 parts by mass per 100 parts by mass of the first copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of 4 or more.

[0031] The content of the first copper particles in the copper paste may be 1 mass% or more, 10 mass% or more, or 20 mass% or more, and 90 mass% or less, 70 mass% or less, or 50 mass% or less, based on the total mass of the metal particles contained in the copper paste. If the content of the first copper particles is within the above range, it is easy to form wiring with excellent conductive reliability.

[0032] The first copper particles may be treated with a surface treatment agent from the viewpoint of dispersion stability and oxidation resistance. The surface treatment agent may be one that is removed during wiring formation (when sintering the copper particles). Examples of the surface treatment agent include aliphatic carboxylic acids such as palmitic acid, stearic acid, arachidic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornylcyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanenitrile; silane coupling agents such as alkylalkoxysilanes; and polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. The surface treatment agent may be used alone or in combination of two or more.

[0033] The amount of the surface treatment agent may be an amount of one molecular layer or more on the particle surface. The amount of the surface treatment agent varies depending on the specific surface area of ​​the first copper particles, the molecular weight of the surface treatment agent, and the minimum coverage area of ​​the surface treatment agent. The amount of the surface treatment agent is usually 0.001 mass% or more.

[0034] The amount of the surface treatment agent is determined by the number of molecular layers (n) attached to the surface of the first copper particles and the specific surface area (A p ) (unit: m 2 / g) and the molecular weight of the surface treatment agent (M s ) (unit: g / mol) and the minimum coverage area of ​​the surface treatment agent (S S ) (unit: m 2 / piece) and Avogadro's number (N A )(6.02×10 23 Specifically, the amount of surface treatment agent can be calculated by the amount of surface treatment agent (mass%) = {(n·A p M s ) / (S S N A +n·A p M s )}×100%.

[0035] The specific surface area of ​​the first copper particles can be calculated by measuring the dried copper particles using a BET specific surface area measurement method. The minimum coverage area of ​​the surface treatment agent is 2.05 × 10 -19 m 2 The carbon content of the surface treatment agent is 1 / molecule. In the case of other surface treatment agents, it can be measured, for example, by calculation from a molecular model or by the method described in "Chemistry and Education" (Katsuhiro Ueda, Sumio Inafuku, Iwao Mori, 40(2), 1992, p114-117). An example of a method for quantifying the surface treatment agent is shown below. The surface treatment agent can be identified by a thermal desorption gas-gas chromatograph mass spectrometer of the dried powder obtained by removing the dispersing medium from the copper paste, and the carbon number and molecular weight of the surface treatment agent can be determined. The carbon content of the surface treatment agent can be analyzed by carbon content analysis. Examples of carbon content analysis methods include high-frequency induction heating furnace combustion / infrared absorption method. The amount of the surface treatment agent can be calculated from the carbon number, molecular weight and carbon content of the identified surface treatment agent using the above formula.

[0036] The first copper particles can be commercially available. Examples of commercially available first copper particles include MA-C025 (manufactured by Mitsui Mining & Smelting Co., Ltd., average particle size 4.1 μm), 3L3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., average particle size 7.3 μm), 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., average particle size 5.8 μm), and 2L3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., average particle size 9 μm).

[0037] When producing a copper paste, it is possible to use copper particles containing first copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of 4 or more, and the content of the copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of less than 2 is 50 parts by mass or less, preferably 30 parts by mass or less, per 100 parts by mass of the first copper particles having a particle size of 2.0 μm or more and 50 μm or less and an aspect ratio of 4 or more. A commercially available product made of such copper particles may be selected and used.

[0038] In one embodiment, the copper paste may include first copper particles and second copper particles having a particle size (maximum diameter) of 0.8 μm or less. In this case, when the copper particles are sintered, the second copper particles are present between the first copper particles, which tends to improve the conductivity of the resulting wiring. In particular, when the first copper particles are used as the copper particles, it is preferable to use the first copper particles and the second copper particles in combination. That is, when the copper paste is prepared from only the second copper particles, the volume shrinkage and sintering shrinkage accompanying drying of the dispersion medium are large, so that the sintered body (wiring) is easily peeled off from the adherend surface when the copper particles are sintered, and it is difficult to obtain sufficient conduction reliability. However, by using the first copper particles and the second copper particles in combination, the volume shrinkage when the copper paste is sintered is suppressed, and the adhesion between the obtained wiring and the polymer molded body, which is the adherend, is improved. Therefore, the wiring is less likely to break due to thermal stress.

[0039] The second copper particles act as copper particles that suitably bond the first copper particles together. In addition, the second copper particles have better sinterability than the first copper particles and have the function of promoting sintering of the copper particles. For example, it becomes possible to sinter the copper particles at a lower temperature than when the first copper particles are used alone.

[0040] The particle size of the second copper particles may be 0.5 μm or less, 0.4 μm or less, or 0.3 μm or less. The particle size of the second copper particles may be 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, or 0.2 μm or more. The average particle size of the second copper particles may be 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, or 0.2 μm or more, and may be 0.8 μm or less, 0.5 μm or less, 0.4 μm or less, or 0.3 μm or less.

[0041] The volume average particle diameter of the second copper particles may be 0.01 μm or more, and may be 0.8 μm or less. If the volume average particle diameter of the second copper particles is 0.01 μm or more, the effects of suppressing the synthesis cost of the second copper particles, good dispersibility, and suppressing the amount of surface treatment agent used are easily obtained. If the volume average particle diameter of the second copper particles is 0.8 μm or less, the effect of excellent sinterability of the second copper particles is easily obtained. From the viewpoint of further achieving the above effects, the volume average particle diameter of the second copper particles may be 0.05 μm or more, 0.1 μm or more, or 0.2 μm or more, and may be 0.5 μm or less, 0.4 μm or less, or 0.3 μm or less.

[0042] The second copper particles may contain 10 mass% or more of copper particles having a particle size of 0.01 μm or more and 0.8 μm or less. From the viewpoint of sinterability of the copper paste, the second copper particles may contain 20 mass% or more, 30 mass% or more, or 100 mass% of copper particles having a particle size of 0.01 μm or more and 0.8 μm or less. When the content ratio of copper particles having a particle size of 0.01 μm or more and 0.8 μm or less in the second copper particles is 20 mass% or more, the dispersibility of the copper particles is further improved, and the increase in viscosity and the decrease in paste concentration can be further suppressed.

[0043] The content of the second copper particles in the copper paste may be 20% by mass or more, 30% by mass or more, 35% by mass or more, or 40% by mass or more, and 90% by mass or less, 85% by mass or less, or 80% by mass or less, based on the total mass of the metal particles contained in the copper paste. If the content of the second copper particles is within the above range, the obtained wiring is less likely to break due to thermal stress.

[0044] The content of the second copper particles in the copper paste may be 20% by mass or more and 90% by mass or less based on the total mass of the first copper particles and the second copper particles. If the content of the second copper particles is 20% by mass or more, the gaps between the first copper particles can be sufficiently filled, and the resulting wiring is less likely to break due to thermal stress. If the content of the second copper particles is 90% by mass or less, the volumetric shrinkage when the copper particles are sintered can be sufficiently suppressed, and the resulting wiring is less likely to break due to thermal stress. From the viewpoint of further achieving the above effect, the content of the second copper particles may be 30% by mass or more, 35% by mass or more, or 40% by mass or more, and may be 85% by mass or less, or 80% by mass or less, based on the total mass of the first copper particles and the second copper particles.

[0045] The shape of the second copper particles may be, for example, spherical, blocky, needle-like, flake-like, approximately spherical, etc. The second copper particles may be an aggregate of copper particles having these shapes. From the viewpoint of dispersibility and packing property, the shape of the second copper particles may be spherical, approximately spherical, or flake-like, and from the viewpoint of combustibility and mixability with the first copper particles, etc., the shape of the second copper particles may be spherical or approximately spherical.

[0046] The aspect ratio of the second copper particles may be 5 or less, or may be 3 or less, from the viewpoints of dispersibility, packing property, and mixability with the first copper particles.

[0047] The second copper particles may be treated with a specific surface treatment agent. Examples of the specific surface treatment agent include organic acids having 8 to 16 carbon atoms. Examples of the organic acids having 8 to 16 carbon atoms include caprylic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, pelargonic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, capric acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnonanoic acid, butyloctanoic acid, Saturated fatty acids such as pentylheptanoic acid, tridecanoic acid, methyldodecanoic acid, ethylundecanoic acid, propyldecanoic acid, butylnonanoic acid, pentyloctanoic acid, myristic acid, methyltridecanoic acid, ethyldodecanoic acid, propylundecanoic acid, butyldecanoic acid, pentylnonanoic acid, hexyloctanoic acid, pentadecanoic acid, methyltetradecanoic acid, ethyltridecanoic acid, propyldodecanoic acid, butylundecanoic acid, pentyldecanoic acid, hexylnonanoic acid, palmitic acid, methylpentadecanoic acid, ethyltetradecanoic acid, propyltridecanoic acid, butyldodecanoic acid, pentylundecanoic acid, hexyldecanoic acid, heptylnonanoic acid, methylcyclohexanecarboxylic acid, ethylcyclohexanecarboxylic acid, propylcyclohexanecarboxylic acid, butylcyclohexanecarboxylic acid, pentylcyclohexanecarboxylic acid, hexylcyclohexanecarboxylic acid, heptylcyclohexanecarboxylic acid, octylcyclohexanecarboxylic acid, and nonylcyclohexanecarboxylic acid; octene Examples of the organic acid include unsaturated fatty acids such as benzoic acid, nonenoic acid, methylnonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, and sabienoic acid; and aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, and nonylbenzoic acid. The organic acid may be used alone or in combination of two or more.By combining such an organic acid with the second copper particles, it tends to be possible to achieve both the dispersibility of the second copper particles and the desorption property of the organic acid during sintering.

[0048] The amount of the surface treatment agent may be an amount that adheres to the surface of the second copper particles in a monolayer to trilayer form. The amount of the surface treatment agent may be 0.07% by mass or more, 0.10% by mass or more, or 0.2% by mass or more, and may be 2.1% by mass or less, 1.6% by mass or less, or 1.1% by mass or less. The amount of the surface treatment agent of the second copper particles can be calculated by the method described above for the first copper particles. The same applies to the specific surface area, the molecular weight of the surface treatment agent, and the minimum coverage area of ​​the surface treatment agent.

[0049] The second copper particles can be commercially available. Examples of commercially available second copper particles include CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 0.36 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 0.72 μm), and Tn-Cu100 (manufactured by Taiyo Nippon Sanso Co., Ltd., volume average particle size 0.12 μm).

[0050] The total content of the first copper particles and the second copper particles in the copper paste may be 80% by mass or more based on the total mass of the metal particles contained in the copper paste. If the total content of the first copper particles and the second copper particles is within the above range, the resulting wiring is less likely to break due to thermal stress. From the viewpoint of further achieving the above effect, the total content of the first copper particles and the second copper particles may be 90% by mass or more, 95% by mass or more, or even 100% by mass based on the total mass of the metal particles.

[0051] The copper paste may further contain other metal particles other than copper particles. Examples of other metal particles include nickel, silver, gold, palladium, platinum, and the like. The volume average particle size of the other metal particles may be 0.01 μm or more or 0.05 μm or more, and may be 10 μm or less, 5.0 μm or less, or 3.0 μm or less. When other metal particles are contained, the content thereof may be less than 20 mass% or may be 10 mass% or less based on the total mass of the metal particles contained in the copper paste from the viewpoint of obtaining sufficient bonding properties. Other metal particles may not be contained. The shape of the other metal particles is not particularly limited.

[0052] By including metal particles other than copper particles, it is possible to obtain wiring in which multiple types of metals are dissolved or dispersed, which improves the mechanical properties of the wiring, such as yield stress and fatigue strength, and tends to improve the electrical conductivity reliability. In addition, by adding multiple types of metal particles, the bonding strength of the formed wiring to a specific adherend (e.g., LCP) tends to be improved, and the electrical conductivity reliability tends to be improved.

[0053] The dispersion medium contained in the copper paste is not particularly limited, and may be, for example, a volatile one. Examples of volatile dispersion media include monohydric and polyhydric alcohols such as pentanol, hexanol, heptanol, octanol, decanol, ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, α-terpineol, and isobornylcyclohexanol; ethylene glycol butyl ether, ethylene glycol phenyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, triethylene glycol methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl ether, propylene glycol propyl ether, and dipropylene glycol methyl ether. ethers such as ether, dipropylene glycol ethyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether; esters such as ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate (DPMA), ethyl lactate, butyl lactate, γ-butyrolactone, and propylene carbonate; acid amides such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; aliphatic hydrocarbons such as cyclohexane, octane, nonane, decane, and undecane; aromatic hydrocarbons such as benzene, toluene, and xylene; mercaptans having an alkyl group having 1 to 18 carbon atoms; and mercaptans having a cycloalkyl group having 5 to 7 carbon atoms.Examples of mercaptans having an alkyl group having 1 to 18 carbon atoms include ethyl mercaptan, n-propyl mercaptan, i-propyl mercaptan, n-butyl mercaptan, i-butyl mercaptan, t-butyl mercaptan, pentyl mercaptan, hexyl mercaptan, and dodecyl mercaptan. Examples of mercaptans having a cycloalkyl group having 5 to 7 carbon atoms include cyclopentyl mercaptan, cyclohexyl mercaptan, and cycloheptyl mercaptan.

[0054] The content of the dispersion medium may be 5 parts by mass or more and 50 parts by mass or less, where the total mass of the metal particles contained in the copper paste is 100 parts by mass. If the content of the dispersion medium is within the above range, the viscosity of the copper paste can be adjusted to a more appropriate value, and the sintering of the copper particles is not easily inhibited.

[0055] If necessary, the copper paste may contain appropriate additives such as wetting improvers, such as nonionic surfactants and fluorine-based surfactants; antifoaming agents, such as silicone oil; and ion trapping agents, such as inorganic ion exchangers.

[0056] The above-mentioned copper paste can be prepared by mixing copper particles and any components (additives, other metal particles, etc.) in a dispersion medium. After mixing the components, a stirring process may be performed. The maximum diameter of the dispersion may be adjusted by a classification operation.

[0057] The copper paste may be prepared by mixing the second copper particles, the surface treatment agent, and the dispersion medium in advance, performing a dispersion treatment to prepare a dispersion of the second copper particles, and further mixing the first copper particles, other metal particles, and any additives. By adopting such a procedure, the dispersibility of the second copper particles is improved, and the mixability with the first copper particles is improved, and the performance of the copper paste is further improved. The dispersion of the second copper particles may be subjected to a classification operation to remove aggregates.

[0058] (Second step). As shown in FIG. 1(c), the copper particles are sintered to form a copper wiring 3.

[0059] The sintering can be performed by a heat treatment, for example, a heating means such as a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, or a steam heating furnace can be used for the heat treatment.

[0060] The atmosphere during sintering may be an oxygen-free atmosphere from the viewpoint of suppressing oxidation of the sintered body, or a reducing atmosphere from the viewpoint of removing surface oxides of copper particles in the copper paste layer 2. Examples of the oxygen-free atmosphere include an oxygen-free gas such as nitrogen or a rare gas, or a vacuum. Examples of the reducing atmosphere include a pure hydrogen gas atmosphere, a mixed gas of hydrogen and nitrogen such as forming gas, nitrogen containing formic acid gas, a mixed gas of hydrogen and a rare gas, and a rare gas containing formic acid gas.

[0061] The maximum temperature reached during the heat treatment may be 150°C or higher, and may be 350°C or lower, 300°C or lower, or 260°C or lower, from the viewpoint of reducing thermal damage to each component and improving yield. If the maximum temperature reached is 150°C or higher, sintering tends to proceed sufficiently when the maximum temperature reached is held for 60 minutes or less. From the viewpoint of volatilizing all the dispersion medium and improving yield, the maximum temperature reached may be held for 1 minute or more, and may be 60 minutes or less, 40 minutes or less, or 30 minutes or less.

[0062] The copper content (volume ratio) in the copper wiring 3 is preferably 65% ​​by volume or more, more preferably 70% by volume or more, and even more preferably 80% by volume or more, based on the total volume of the copper wiring. By making the copper content in the copper wiring 3 65% by volume or more, good conduction reliability can be obtained. The copper content (volume ratio) in the copper wiring 3 is preferably 95% by volume or less, based on the total volume of the copper wiring. In this case, the copper wiring 3 has voids. When the copper wiring 3 has a suitable void, when a solder paste containing a resin component is applied to the surface of the copper wiring 3 opposite to the surface in contact with the polymer molded body 1, the resin component is easily filled into the voids inside the copper wiring 3, and the resin reaches and hardens in the voids 3a between the copper wiring 3 in contact with the polymer molded body, so that the adhesive strength between the polymer molded body 1 and the copper wiring 3 can be further improved.

[0063] When the composition of the material constituting the copper wiring 3 is known, the copper content in the copper wiring 3 can be found, for example, by the following procedure. First, the copper wiring 3 is cut into a rectangular parallelepiped, and the length and width of the copper wiring 3 are measured with a vernier caliper or an external shape measuring device, and the thickness is measured with a film thickness meter to calculate the volume of the copper wiring 3. The apparent density M1 (g / cm) is calculated from the volume of the cut copper wiring 3 and the weight of the copper wiring 3 measured with a precision balance. 3 ) is calculated. The calculated M1 and the density of copper, 8.96g / cm 3 Using these values, the copper content (volume %) in the copper wiring 3 can be calculated from the following formula (A). Copper content (volume %) in copper wiring 3 = [(M1) / 8.96] × 100 (A)

[0064] The proportion of copper element in the elements excluding light elements among the constituent elements of the copper wiring 3 may be 95 mass% or more, 97 mass% or more, 98 mass% or more, or even 100 mass%. If the proportion of copper element in the copper wiring 3 is within the above range, it is possible to suppress the formation of intermetallic compounds or the precipitation of different elements at the metallic copper crystal boundaries, and the properties of the metallic copper constituting the copper wiring 3 are likely to be strengthened, making it easier to obtain even better connection reliability. In addition, when the proportion of copper element in the elements excluding light elements in the copper wiring 3 is 100 mass%, the volumetric proportion of copper can be regarded as compactness (%).

[0065] The copper wiring 3 preferably includes a structure derived from first copper particles oriented approximately parallel to the bonding interface with the polymer molded body 1 (for example, the bonding surface between the polymer molded body 1 and the copper wiring 3). In this case, by orienting the first particles approximately parallel to the polymer molded body 1, cracks in the copper wiring 3 formed by sintering can be suppressed. Furthermore, although the reason is not clear, the adhesion between the copper wiring 3 formed by sintering and the polymer molded body 1 can be improved.

[0066] (Third step) 1(d), a solder paste containing solder particles 4 and a resin component 5 is applied in a predetermined pattern onto the copper wiring 3 to form a solder paste layer 6. A portion of the resin component 5 permeates into the voids 3a of the copper wiring 3 to form a resin filled portion 7 that fills at least a portion of the copper wiring 3.

[0067] The particle size of the solder particles 4 may be, for example, 0.4 to 30 μm, 0.5 to 20 μm, or 0.6 to 15 μm. When the particle size of the solder particles 4 is 0.4 μm or more, the solder particles are less susceptible to the effect of oxidation of the solder surface, and the electrical continuity reliability is easily improved. On the other hand, when the particle size of the solder particles 4 is 30 μm or less, the insulation reliability is easily improved.

[0068] The particle size of the solder particles 4 can be measured by observation using a scanning electron microscope (SEM). That is, the average particle size of the solder particles is obtained by measuring the particle sizes of 300 random solder particles by observation using a SEM and averaging the particle sizes.

[0069] The solder particles 4 contain tin. As the solder particles 4, at least one tin alloy selected from the group consisting of an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy may be used. Examples of tin alloys include In-Sn (52% by mass In, 48% by mass Bi, melting point 118°C), In-Sn-Ag (20% by mass In, 77.2% by mass Sn, 2.8% by mass Ag, melting point 175°C), Sn-Bi (43% by mass Sn, 57% by mass Bi, melting point 138°C), Sn-Bi-Ag (42% by mass Sn, 57% by mass Bi, 1% by mass Ag, melting point 139°C), Sn-Ag-Cu (96.5% by mass Sn, 3% by mass Ag, 0.5% by mass Cu, melting point 217°C), and Sn-Cu (99.3% by mass Sn, 0.7% by mass Cu, melting point 227°C).

[0070] The tin alloy can be selected according to the joining temperature. For example, when using a tin alloy with a low melting point such as an In-Sn alloy or an Sn-Bi alloy, joining can be performed at 150°C or less. When using a tin alloy with a high melting point such as an Sn-Ag-Cu or Sn-Cu alloy, high reliability tends to be achieved even after exposure to high temperatures.

[0071] The tin alloy constituting the solder particles 4 may contain at least one selected from Ag, Cu, Ni, Bi, Zn, Pd, Pb, Au, P, and B. Of these elements, Ag or Cu may be contained for the following reasons: When the solder particles 4 contain Ag or Cu, the melting point of the solder particles can be lowered to about 220° C., and the bonding strength with the electrode is improved, thereby providing good electrical connection reliability.

[0072] The Cu content of the solder particles 4 may be, for example, 0.05 to 10 mass%, 0.1 to 5 mass%, or 0.2 to 3 mass%. If the Cu content is 0.05 mass% or more, good solder connection reliability is easily obtained, and if the Cu content is 10 mass% or less, the melting point of the solder particles is lowered and the solder wettability is improved, which results in good connection reliability of the joints.

[0073] The Ag content of the solder particles 4 may be, for example, 0.05 to 10 mass%, 0.1 to 5 mass%, or 0.2 to 3 mass%. If the Ag content is 0.05 mass% or more, good solder connection reliability is easily obtained, while if it is 10 mass% or less, the melting point is lowered and solder wettability is improved, which results in good connection reliability of the joints.

[0074] The resin component 5 may contain a thermosetting compound. Examples of the thermosetting compound include an oxetane compound, an epoxy compound, an episulfide compound, a (meth)acrylic compound, a phenol compound, an amino compound, an unsaturated polyester compound, a polyurethane compound, a silicone compound, and a polyimide compound. Among them, an epoxy compound is preferable from the viewpoint of further improving the curability and viscosity of the resin component and further increasing the adhesion between the polymer molded body 1 and the copper wiring 3.

[0075] The resin component 5 may further include a heat curing agent. Examples of the heat curing agent include imidazole curing agent, amine curing agent, phenol curing agent, polythiol curing agent, acid anhydride, thermal cationic initiator, and thermal radical generator. The heat curing agent may be used alone or in combination of two or more. In that it can be cured quickly at low temperature, imidazole curing agent, polythiol curing agent, or amine curing agent is preferable. In addition, in that it enhances the storage stability when the heat curing compound and the heat curing agent are mixed, a latent heat curing agent may be used as the heat curing agent. The latent heat curing agent is preferably a latent imidazole curing agent, a latent polythiol curing agent, or a latent amine curing agent. The heat curing agent may be coated with a polymeric substance such as a polyurethane resin or a polyester resin.

[0076] Examples of imidazole curing agents include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct.

[0077] Examples of polythiol curing agents include trimethylolpropane tris-3-mercaptopropionate, pentaerythritol tetrakis-3-mercaptopropionate, and dipentaerythritol hexa-3-mercaptopropionate. The solubility parameter of the polythiol curing agent is preferably 9.5 or more, and preferably 12 or less. The solubility parameter is calculated by the Fedors method. For example, the solubility parameter of trimethylolpropane tris-3-mercaptopropionate is 9.6, and the solubility parameter of dipentaerythritol hexa-3-mercaptopropionate is 11.4.

[0078] Amine curing agents include, for example, hexamethylenediamine, octamethylenediamine, decamethylenediamine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraspiro[5.5]undecane, bis(4-aminocyclohexyl)methane, metaphenylenediamine, and diaminodiphenylsulfone.

[0079] Examples of the thermal cationic curing agent include iodonium cationic curing agent, oxonium cationic curing agent, and sulfonium cationic curing agent. Examples of the iodonium cationic curing agent include bis(4-tert-butylphenyl)iodonium hexafluorophosphate. Examples of the oxonium cationic curing agent include trimethyloxonium tetrafluoroborate. Examples of the sulfonium cationic curing agent include tri-p-tolylsulfonium hexafluorophosphate.

[0080] Examples of the thermal radical generator include azo compounds and organic peroxides. Examples of the azo compounds include azobisisobutyronitrile (AIBN). Examples of the organic peroxides include di-tert-butyl peroxide and methyl ethyl ketone peroxide.

[0081] The resin component 5 may further contain flux, which melts oxides on the solder surface, fuses the particles together, and improves the solder wettability to the copper wiring 3.

[0082] As the flux, a flux generally used for solder joints and the like can be used. Examples of the flux include zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic halide, hydrazine, an organic acid, and rosin. The flux may be used alone or in combination of two or more kinds.

[0083] The molten salt may be, for example, ammonium chloride. The organic acid may be, for example, lactic acid, citric acid, stearic acid, glutamic acid, and glutaric acid. The rosin may be, for example, activated rosin and non-activated rosin. Rosin is a rosin containing abietic acid as the main component. By using an organic acid or rosin having two or more carboxyl groups as the flux, the effect of further increasing the reliability of conduction between electrodes is achieved.

[0084] The melting point of the flux is preferably 50°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher. The melting point of the flux is preferably 200°C or lower, more preferably 160°C or lower, even more preferably 150°C or lower, and particularly preferably 140°C or lower. When the melting point of the flux is within the above range, the flux effect is more effectively exerted, and the solder particles are more efficiently arranged on the electrodes. The melting point of the flux is preferably in the range of 80 to 190°C, and more preferably 80 to 140°C or lower.

[0085] Examples of fluxes having a melting point in the range of 80 to 190°C include dicarboxylic acids such as succinic acid (melting point 186°C), glutaric acid (melting point 96°C), adipic acid (melting point 152°C), pimelic acid (melting point 104°C), and suberic acid (melting point 142°C), benzoic acid (melting point 122°C), and malic acid (melting point 130°C).

[0086] (Fourth step) Following the third step, an electronic element 8 having an electrode 9 is disposed (mounted) at a predetermined position on the solder paste layer 6 (fourth step), as shown in (e) of Fig. 1. Examples of the electronic element 8 include power modules consisting of diodes, rectifiers, thyristors, MOS gate drivers, power switches, power MOSFETs, IGBTs, Schottky diodes, fast recovery diodes, etc., transmitters, amplifiers, LED modules, capacitors, gyro sensors, etc.

[0087] Examples of a method for placing the electronic element 8 on the solder paste layer 6 include a method using a chip mounter, a flip chip bonder, a carbon or ceramic positioning jig, or the like.

[0088] The electrode 9 may be an electrode containing at least one metal selected from the group consisting of copper, nickel, palladium, gold, platinum, silver and tin on its outermost surface, and is preferably an electrode containing at least one metal selected from the group consisting of copper, nickel and palladium on its outermost surface, from the viewpoint of achieving highly reliable mounting without forming impurities (intermetallic compounds) between the solder layer 11 and the electrode 9 even when left at high temperatures after bonding with the solder layer 11. The electrode 9 may be made of a single or multiple metal-containing layers containing these metals.

[0089] (5th step) Following the fourth step, as shown in (f) of Fig. 1, the solder particles 4 are melted to form a solder layer 11, and the copper wiring 3 and the electrode 9 of the electronic element 8 are joined together (fifth step), thereby obtaining an electronic component 10.

[0090] Heat treatment can be used as a method for melting the solder particles 4. For the heat treatment, a heating means such as a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, or a steam heating furnace can be used.

[0091] The solder particles 4 are melted to form a solder layer 11, which bonds the copper wiring 3 and the electrode 9 of the electronic element 8, and the resin component 5 hardens to form a resin layer 12 that covers at least a part of the solder layer 11. Specifically, in the case of Sn-Bi (Sn 43 mass %, Bi 57 mass %) with a melting point of 138°C, the solder layer 11 is formed by holding at 150°C, and the resin component 5 covers the outer periphery of the solder layer 11 and hardens to become the resin layer 12. At this time, the resin component that has filled at least a part of the void portion 3a of the copper wiring 3 hardens to form a resin filled portion 13.

[0092] The atmosphere during solder bonding may be an oxygen-free atmosphere from the viewpoint of suppressing oxidation of the sintered body, or a reducing atmosphere from the viewpoint of removing surface oxides of the copper wiring 3. Examples of the oxygen-free atmosphere include an oxygen-free gas such as nitrogen or a rare gas, or a vacuum. Examples of the reducing atmosphere include a pure hydrogen gas atmosphere, a mixed gas of hydrogen and nitrogen such as forming gas, nitrogen containing formic acid gas, a mixed gas of hydrogen and a rare gas, and a rare gas containing formic acid gas.

[0093] From the viewpoint of reducing thermal damage to each component and improving yield, the maximum temperature reached during the heat treatment may be 150° C. or higher, and may be 350° C. or lower, 300° C. or lower, or 260° C. or lower. If the maximum temperature reached is 150° C. or higher, melting of the solder particles 4 tends to proceed sufficiently when the maximum temperature is held for 60 minutes or less.

[0094] The soldering may be performed with pressure applied to the electronic element 8, or may be performed only by the weight of the electronic element 8 and other members on the solder paste layer 6. The pressure may be 0.01 MPa or less, or 0.005 MPa or less. If the pressure applied during sintering is within the above range, no special pressurizing device is required, and it is possible to further reduce voids and improve the bonding strength and connection reliability without impairing the yield. Examples of methods for applying pressure to the electronic element 8 include a method of placing a weight on the uppermost electronic element 8.

[0095] The electronic component 10 obtained by the manufacturing method described above includes a polymer molded body 1, a copper wiring 3 provided on the polymer molded body 1, a solder layer 11 that joins the copper wiring 3 and an electronic element 8, and a resin layer 12 that covers at least a portion of the solder layer 11. At least a portion of the voids 3a in the copper wiring 3 is filled with a cured product of the same resin component as the resin layer 12.

[0096] 2 is a diagram showing details of a joint between a copper wiring 3 and a polymer molded body 1 in an electronic component 10. A void 3a of the copper wiring 3 is formed at the interface with the polymer molded body 1, and a resin component is filled into the void 3a and hardens to become a resin filled portion 13, making it possible to improve the adhesion between the copper wiring 3 and the polymer molded body 1.

[0097] FIG. 3 is a schematic cross-sectional view showing a method for manufacturing an electronic component according to another embodiment. Hereinafter, this embodiment will be described, but the description overlapping with the above-mentioned embodiment will be omitted. In this manufacturing method, in the preparation step of the first step, a polymer molded body 1 is prepared as shown in FIG. 3(a) (preparation step). In the first step, following the preparation step, as shown in FIG. 3(b), a copper paste is applied in a predetermined pattern (on the portion where the copper wiring is to be formed) on the polymer molded body 1 to form a copper paste layer 2 (formation step). Then, as shown in FIG. 3(c), the copper particles are sintered together to form copper wiring 3. (Second step).

[0098] Next, as shown in FIG. 3(d), a resin layer 14 containing a resin component is formed on a part of the copper wiring 3. The resin component is filled into at least a part of the voids 3a of the copper wiring 3 to obtain a resin-filled part 15. The resin component may be the same as the resin component 5 of the solder paste described above. When the resin component and the resin component 5 are the same, the resin layer 14 may be applied to the entire surface of the copper wiring 3 and the polymer molded body 1. A solder paste containing solder particles 4 and the resin component 5 may be applied to the upper part of the resin layer 14 applied on the copper wiring 3. The resin layer 14 may be formed in a place other than the copper wiring 3 to which the electronic element 8 is bonded, and may or may not be cured in advance. The atmosphere during curing of the resin layer 14 may be an oxygen-free atmosphere or a reducing atmosphere from the viewpoint of suppressing oxidation of the copper wiring 3. Examples of the oxygen-free atmosphere include the introduction of an oxygen-free gas such as nitrogen or a rare gas, or a vacuum. Examples of the reducing atmosphere include pure hydrogen gas, a mixed gas of hydrogen and nitrogen such as forming gas, nitrogen containing formic acid gas, a mixed gas of hydrogen and a rare gas, and a rare gas containing formic acid gas.

[0099] Next, as shown in FIG. 3(e), the solder paste is applied onto the predetermined copper wiring 3 in a predetermined pattern (third step). The resin component 5 permeates into the voids 3a of the copper wiring 3 and fills at least a part of the copper wiring 3. Following the third step, as shown in FIG. 3(f), an electronic element 8 having an electrode 9 is disposed (mounted) at a predetermined position on the solder paste layer 6 (fourth step). Following the fourth step, as shown in FIG. 3(g), the solder particles 4 are melted to form a solder layer 11, and the copper wiring 3 and the electrode 9 of the electronic element 8 are joined (fifth step). The resin layer 14 is hardened to become a resin layer 16. This results in an electronic component 18.

[0100] An electronic component 18 obtained by the manufacturing method described above includes a polymer molded body 1, a copper wiring 3 provided on the polymer molded body 1, a solder layer 11 that joins the copper wiring 3 to an electrode 9 of an electronic element 8, a resin layer 12 that covers at least a portion of the solder layer 11, and a resin layer 16 that covers a portion of the copper wiring 3. At least a portion of a void 3a in the copper wiring 3 is filled with a cured product of the same resin component as the resin layer 12 or the resin layer 16.

[0101] In the manufacturing method of the electronic component according to the present embodiment, the copper paste is applied in a predetermined pattern (a pattern corresponding to the copper wiring 3), so that a polymer containing a catalyst is not required, and the steps of laser irradiation and electroless copper plating can be omitted. In addition, in these manufacturing methods, after the paste layer 6 is formed on the copper wiring 3, the electronic element 8 is arranged and heat-treated, whereby the copper wiring 3 and the electronic element 8 are joined to each other by solder, at least a part of the solder layer 11 is covered with the resin layer 12, and the resin component filled in at least a part of the voids in the copper wiring 3 is cured to form the resin filled portion 13 or the resin filled portion 17, thereby improving the adhesion between the polymer molded body and the copper wiring.

[0102] In the manufacturing method of this embodiment, the resin layer 14 containing a resin component that covers a portion of the copper wiring 3 and the resin component 5 in the solder paste are made of the same component, so that the solder bonding between the electronic element 8 and the copper wiring 3 and the production of a surface protective coating for the copper wiring 3 can be performed in the same process. This allows the process and manufacturing time to be significantly shortened compared to conventional processes (such as a solder resist formation process (application of an organic coating to the copper wiring and the front surface of the polymer molding, exposure, and development to form openings for solder bonding), application of solder paste to the wiring openings, and a solder bonding process (component mounting) by heat treatment).

[0103] FIG. 4 is an SEM image showing an example of a cross section of a copper wiring made of a sintered body of copper particles. The copper wiring 24 shown in FIG. 4 has a structure derived from flake-shaped copper particles oriented approximately parallel to the bonding interface (for example, the bonding surface between the polymer molded body and the wiring). When the wiring has the above-mentioned copper wiring 24, cracking of the wiring can be suppressed by orienting the flake-shaped copper particles approximately parallel to the bonding interface direction. Furthermore, although the reason is unclear, the adhesion between the wiring and the polymer molded body can be improved.

[0104] 4 may further include voids 24b and sintered copper derived from copper particles (e.g., spherical copper particles) that bond the flaky copper particles together, in addition to sintered copper 24a derived from the flaky copper particles. The wiring having the copper wiring 24 can be formed, for example, by sintering a copper paste that includes flaky copper particles and, in some cases, copper particles (e.g., spherical copper particles) that bond the flaky copper particles together.

[0105] Here, the flake shape includes flat shapes such as plate-like and scale-like. In the sintered copper 24a derived from the flaky copper particles contained in the above structure, the ratio of the major axis (maximum diameter) to the thickness (major axis / thickness, aspect ratio) may be 5 or more. The number average diameter of the major axis may be 2.0 μm or more, 3.0 μm or more, or 4.0 μm or more. When the sintered copper 24a derived from the flaky copper particles has such a shape, the reinforcing effect of the copper wiring 24 contained in the wiring is improved, and the adhesion (bonding strength) between the wiring and the polymer molded body and the conductive reliability of the wiring are further improved.

[0106] The major axis and thickness of the sintered copper 24a derived from the flake-like copper particles can be obtained, for example, from an SEM image of the cross section of the wiring. The following is an example of a method for measuring the major axis and thickness of the sintered copper derived from the flake-like copper particles from an SEM image. First, the wiring is cut into a rectangular parallelepiped shape to be used as a measurement sample. The sample is placed in a casting cup, and epoxy casting resin is poured into the cup so that the entire sample is buried, and then hardened. The cast sample is cut near the cross section to be observed, and the cross section is polished and processed with a CP (cross section polisher). The cross section of the sample is observed at 5000 times with an SEM device. A cross-sectional image of the wiring (e.g., 5000x magnification) is obtained, and for dense, continuous linear, rectangular, or ellipsoidal parts, the longest line included in this part is taken as the long axis, and the longest line included in this part that is perpendicular to this is taken as the thickness. If the long axis length is 1.0 μm or more and the long axis / thickness ratio is 4 or more, it is considered to be sintered copper derived from flake-like copper particles, and the long axis and thickness of the sintered copper derived from flake-like copper particles are measured using image processing software with a length measurement function. The average values ​​are obtained by calculating the number average of 20 or more randomly selected points.

[0107] In the above embodiment, the copper particles are used as the metal particles, but the metal particles according to the present embodiment are not limited to copper particles. Particles containing a sinterable metal can be used. Even when metal particles other than copper particles are used, the above-mentioned manufacturing process for electronic components can be applied. EXAMPLES

[0108] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0109] [Preparation of copper paste] (Copper paste A1) 5.2 g of α-terpineol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 6.8 g of isobornylcyclohexanol (manufactured by Nippon Terpene Chemical Co., Ltd.) as a dispersion medium, and 52.8 g of "CH-0200" (manufactured by Mitsui Mining & Smelting Co., Ltd., 50% volume average particle size: 0.36 μm, content of copper particles with a particle size of 0.01 to 0.8 μm: 95% by mass) as submicro copper particles were mixed in a plastic bottle, and the mixture was treated with an ultrasonic homogenizer (trade name "US-600" manufactured by Nippon Seiki Co., Ltd.) at 19.6 kHz, 600 W, and 1 minute to obtain a dispersion liquid. 35.2 g of "MA-C025" (manufactured by Mitsui Mining & Smelting Co., Ltd., content of copper particles with a maximum diameter of 1 to 20 μm: 100% by mass) as flake-shaped micro copper particles was added to this dispersion liquid, and the mixture was stirred with a spatula until the dry powder disappeared. The plastic bottle was sealed and stirred at 2000 rpm for 2 minutes using a planetary stirring device (manufactured by Thinky Corporation under the trade name "Planetry Vacuum Mixer ARV-310"), and then stirred under reduced pressure at 2000 rpm for 2 minutes to obtain copper paste a1.

[0110] (Copper paste A2) Copper paste a2 was obtained in the same manner as copper paste a1, except that silver-coated copper particles "10% Ag-coated Cu-HWQ 5 μm" (manufactured by Fukuda Metal Foil & Powder Co., Ltd., 50% volume average particle size: 5.89 μm) were used instead of the submicro copper particles, and silver-coated copper particles "10% Ag-coated 2L3" (manufactured by Fukuda Metal Foil & Powder Co., Ltd., 50% volume average particle size: 10.86 μm) were used instead of the flake-shaped micro copper particles.

[0111] [Preparation of solder paste] A solder paste was prepared by mixing 70 parts by mass of solder particles ("Sn42-Bi58 particles", average particle size: 20 μm), 25.2 parts by mass of bisphenol F type epoxy resin ("YDF-170", product name, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., epoxy equivalent: 170), 1.3 parts by mass of an imidazole compound ("2PZ-CN", product name, manufactured by Shikoku Chemical Industry Co., Ltd.), and 3.5 parts by mass of 2,2-bishydroxymethylpropionic acid.

[0112] [Example 1] (Production of electronic component 40) A polymer molded body made of a liquid crystal polymer having a size of 40 mm×40 mm and a thickness of 3 mm (product name "Sumikasuper LCP E6000HF" manufactured by Sumitomo Chemical Co., Ltd.) was prepared. Next, as shown in FIG. 5(a), a stainless steel metal mask (thickness: 50 μm) having two rectangular openings of 1.5 mm×1 mm was placed on the polymer molded body 31, and copper paste a1 was applied by stencil printing using a metal squeegee to obtain a member having a copper paste layer 32.

[0113] The above-mentioned members were set in a tube furnace (manufactured by AVC Corporation), and argon gas was flowed at 1 L / min to replace the air with argon gas. Then, while flowing hydrogen gas at 300 mL / min, a sintering process was performed under the conditions of heating for 10 minutes and then at 180°C for 60 minutes to sinter the copper paste layer 32, thereby forming copper wiring 33 as shown in FIG. 5(b).

[0114] Next, as shown in Fig. 5(c), solder paste was applied onto the copper wiring 33 to form a solder paste layer 34, and then, as shown in Fig. 5(d), a ceramic capacitor 35 (2 mm x 1.2 mm x 0.6 mmt, product name "GQM series" manufactured by Murata Manufacturing Co., Ltd.) having electrodes 36 formed thereon was disposed (mounted) on the solder paste layer 34 to obtain a component. The electrodes 36 were made of copper on both ends of the ceramic capacitor 35.

[0115] Next, the member shown in Fig. 5(d) was placed on a hot plate heated to 170°C in the atmosphere for 15 minutes to obtain electronic component 40. The cross-sectional shape of electronic component 40 is shown in Fig. 5(e). Fig. 5(e) is a cross-sectional view taken along line IVc-IVc in Fig. 5(d). Electrode 36 of ceramic capacitor 35 and copper wiring 33 were joined by solder layer 37, and the outer periphery of the solder joint was reinforced by resin layer 38.

[0116] An electronic component 40 was embedded in casting resin 42 to prepare a sample for cross-sectional observation. FIG. 6 shows the result of cross-sectional observation of electronic component 40 under an optical microscope. Electrode 36 of ceramic capacitor 35 and copper wiring 33 were joined via solder layer 37, and resin layer 38 was formed on the outer periphery of solder layer 37. FIG. 7 shows the result of cross-sectional observation of polymer molded body 31, copper wiring 33 and solder layer 37 under an optical microscope. Copper wiring 33 had voids, and resin component was filled into the voids to form resin filled portions 43.

[0117] (Evaluation of Adhesion) The connection strength (shear strength) of the electronic component 40 was measured using a bond tester (trade name: Universal Bond Tester Series 4000, manufactured by Dage). Specifically, as shown in (a) and (b) of FIG. 10, a shear tool 45 was placed on the electronic component 40 at a shear height of 50 μm, and shearing was performed in the direction of the arrow at a speed of 0.5 mm / min to measure the shear strength. Note that (b) of FIG. 10 is a cross-sectional view taken along line IVc-IVc in (d) of FIG. 5. The adhesion between the polymer molded body 31 and the copper wiring 33 was evaluated from the average value of the shear strength at 20 points where the polymer molded body 31 and the copper wiring 33 were joined. The results are shown in Table 1.

[0118] (Production of Electronic Component 44) The polymer molded body was prepared, and as shown in (a) of FIG. 8, a stainless steel metal mask (thickness: 50 μm) having one square opening of 0.9 mm×0.9 mm was placed on the polymer molded body 31, and copper paste a1 was applied by stencil printing using a metal squeegee to obtain a member having a copper paste layer 32. The obtained member was set in a tube furnace (manufactured by AVC Corporation), and argon gas was flowed at 1 L / min to replace the air with argon gas. Thereafter, the copper paste layer was sintered by sintering under the conditions of heating for 10 minutes and at 180° C. for 60 minutes while flowing hydrogen gas at 300 mL / min, and copper wiring 33 was formed as shown in (b) of FIG. 8.

[0119] Next, as shown in FIG. 8(c), solder paste was applied onto the copper wiring to form a solder paste layer 34. Next, as shown in FIG. 8(d), a copper substrate 39 (1 mm×1 mm×0.3 mmt) was mounted on the solder paste layer 34 to obtain a component. Next, the component shown in FIG. 8(d) was placed on a hot plate heated to 170° C. in the atmosphere and left for 15 minutes. The cross-sectional shape of the electronic component 44 obtained by leaving it is shown in FIG. 8(e). The copper substrate 39 and the copper wiring 33 were joined by the solder layer 37, and the outer periphery of the solder layer 37 was reinforced by the resin layer 38.

[0120] 9 shows the result of observation of a cross section of electronic component 44 by an optical microscope. Copper substrate 39 and copper wiring 33 are joined via solder layer 37, and resin layer 38 is formed on the outer periphery of solder layer 37.

[0121] (Evaluation of Adhesion) The connection strength (shear strength) of the electronic component 44 was measured using a bond tester. Specifically, as shown in FIG. 11, a shear tool 45 was placed on the electronic component 44 at a shear height of 50 μm, and shearing was performed in the direction of the arrow at a speed of 0.5 mm / min to measure the shear strength. The adhesion between the polymer molded body 31 and the copper wiring 33 was evaluated from the average value of the shear strength at 20 points where the polymer molded body 31 and the copper wiring 33 were joined. The results are shown in Table 1.

[0122] [Example 2] Except for changing the sintering temperature of copper paste layer 32 from 180° C. to 225° C., electronic components 40 and 44 were produced in the same manner as in Example 1, and their adhesiveness was evaluated.

[0123] [Example 3] Electronic components 40 and 44 were produced in the same manner as in Example 1, except that copper paste a2 was used instead of copper paste a1 to form copper paste layer 32, and copper paste layer 32 was fired at 180°C for 10 minutes in air, and adhesiveness was evaluated.

[0124] [Comparative Example 1] Electronic component 48 shown in FIG. 12 and electronic component 49 shown in FIG. 13 were produced in the same manner as in Example 1, except that solder layer 37 was formed using only solder particles “Sn42-Bi58 particles” instead of solder paste, and adhesion was evaluated.

[0125] [Comparative Example 2] Electronic components 48 and 49 were produced in the same manner as in Example 2, except that solder layer 37 was formed using only solder particles “Sn42-Bi58 particles” instead of solder paste, and their adhesion was evaluated.

[0126] [Comparative Example 3] Electronic components 48 and 49 were produced in the same manner as in Example 3, except that solder layer 37 was formed using only solder particles “Sn42-Bi58 particles” instead of the solder paste, and their adhesion was evaluated.

[0127] [Table 1] [Explanation of symbols]

[0128] 1,31...polymer molded body, 2,32...copper paste layer, 3,24,33...copper wiring, 3a...void portion, 4...solder particle, 5...resin component, 6,34...solder paste layer, 7,13,15,17,43...resin filled portion, 8...electronic element, 35...ceramic capacitor, 9,36...electrode, 10,40,44,48,49...electronic component, 11,37...solder layer, 12,14,16,38...resin layer, 39...copper substrate, 42...cast resin, 45...share tool.

Claims

1. A first step of applying a metal paste containing metal particles including copper particles and a volatile dispersion medium onto a polymer molded body in a predetermined pattern to form a metal paste layer; a second step of forming a metal wiring by sintering the metal particles; a third step of applying a solder paste containing solder particles and a resin component onto the metal wiring to form a solder paste layer; a fourth step of placing an electronic element on the solder paste layer; a fifth step of heating the solder paste layer to form a solder layer that joins the metal wiring and the electronic element and to form a resin layer that covers at least a portion of the solder layer; A method for manufacturing an electronic component, wherein in the second step, the metal wiring has voids, and in the third step, at least a portion of the voids is filled with the resin component.

2. The method of claim 1 , wherein the solder particles include tin.

3. 3. The method for producing an electronic component according to claim 2, wherein the solder particles are made of at least one tin alloy selected from the group consisting of an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy.

4. The method for producing an electronic component according to any one of claims 1 to 3, wherein the polymer molded body is made of a liquid crystal polymer or polyphenylene sulfide.

5. the electronic element has an electrode containing at least one selected from the group consisting of copper, nickel, palladium, gold, platinum, silver, and tin on its outermost surface, 5. The method for producing an electronic component according to claim 1, wherein in the fourth step, the electronic element is disposed so that the electrodes are in contact with the solder paste layer.

6. A method for manufacturing an electronic component described in any one of claims 1 to 5, wherein the resin component contains at least one thermosetting compound selected from the group consisting of oxetane compounds, epoxy compounds, episulfide compounds, (meth)acrylic compounds, phenol compounds, amino compounds, polyurethane compounds, silicone compounds and polyimide compounds.

7. The method for producing an electronic component according to any one of claims 1 to 6, wherein the metal particles include first copper particles having a particle size of 2.0 μm or more and second copper particles having a particle size of 0.8 μm or less.

8. A polymer molding; a metal wiring formed on the polymer molded body and made of a sintered body of metal particles including copper particles; An electronic element disposed on the metal wiring; a solder layer that bonds the metal wiring and the electronic element; a resin layer made of a cured product of a resin component that covers at least a portion of the solder layer; Equipped with the metal wiring has a void, and at least a portion of the void is filled with a cured product of the resin component; The electronic component, wherein the resin component contains at least one thermosetting compound selected from the group consisting of an oxetane compound, an epoxy compound, an episulfide compound, a (meth)acrylic compound, a phenol compound, an amino compound, a polyurethane compound, a silicone compound, and a polyimide compound.

9. The electronic component of claim 8 , wherein the solder layer comprises tin.

10. The electronic component according to claim 9, wherein the solder layer is made of at least one tin alloy selected from the group consisting of an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy.

11. The electronic component according to any one of claims 8 to 10, wherein the polymer molded body is made of a liquid crystal polymer or polyphenylene sulfide.

12. the electronic element has an electrode containing at least one selected from the group consisting of copper, nickel, palladium, gold, platinum, silver, and tin on its outermost surface, The electronic component according to any one of claims 8 to 11, wherein the electrode is bonded to the solder layer.

13. The electronic component according to any one of claims 8 to 12, wherein the metal particles include first copper particles having a particle size of 2.0 μm or more and second copper particles having a particle size of 0.8 μm or less.